The Influence Of The Family Environment And Social Media On Entrepreneurial Interest (Case Study On Students Of Smkn 4 Garut) - Mira Veranita; Dermawan Supriatna; Aam Pathuloh; Dyah Bayu Framesthi; Raya Mustiraya (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2023)
Abstract The research conducted using quantitative methods with an associative approach was conducted on 258 students, with the aim of determining the influence of family and social media on students' entrepreneurial desires. The results showed that the family has a considerable influence in building students' desire for entrepreneurship. Students who live in open-minded families, develop a positive, courageous, honest, and creative competitive atmosphere will grow into individuals who have great interest and motivation in entrepreneurship. In addition, social media also has a significant influence on entrepreneurial interest. Various information from social media, stories of successful businessmen, brands, products, fashion developments, lifestyle, and other things related to business also affect students' interest in entrepreneurship. This research proves that family environment and social media influence students' entrepreneurial desires. Keywords: Family; Social Media; Entrepreneurship